2021
DOI: 10.1039/d1cp02376d
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state symmetry breaking in 9,10-dicyanoanthracene-based quadrupolar molecules: the effect of donor–acceptor branch length

Abstract: Excited-state symmetry breaking is investigated in a series of symmetric 9,10-dicyanoantracenes linked to electron-donating groups on the 2 and 6 positions via different spacers, allowing for a tuning of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…However, considering that the length of a D–A branch is usually much larger than the size of a solvent molecule, the field perceived by the surrounding medium is certainly not that from a quadrupole or an octupole but rather the field generated by the dipole of the nearby branch. Based on this, the solvation energy of a molecule in a delocalized quadrupolar state was estimated to range from one-eighth to one-half of the solvation energy of the same molecule in a localized dipolar state, depending on the cavity model used . Although a fluorescence solvatochromism as large as that of the single-branched analogue can be considered as evidence of ES-SB, not much can be concluded about the extent of ES-SB in nonpolar or weakly polar environments.…”
Section: Looking At Symmetry-forbidden Vibrational Transitionsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, considering that the length of a D–A branch is usually much larger than the size of a solvent molecule, the field perceived by the surrounding medium is certainly not that from a quadrupole or an octupole but rather the field generated by the dipole of the nearby branch. Based on this, the solvation energy of a molecule in a delocalized quadrupolar state was estimated to range from one-eighth to one-half of the solvation energy of the same molecule in a localized dipolar state, depending on the cavity model used . Although a fluorescence solvatochromism as large as that of the single-branched analogue can be considered as evidence of ES-SB, not much can be concluded about the extent of ES-SB in nonpolar or weakly polar environments.…”
Section: Looking At Symmetry-forbidden Vibrational Transitionsmentioning
confidence: 99%
“…55 The validity of this idea was demonstrated with the twobranched dyes 8 and 9. 17,55 Occurrence of ES-SB with 8 in polar solvents was inferred from the IR TA spectra in the −CC− stretching region showing the rise of a second −CC− band around 2150 cm −1 , which is absent in nonpolar solvents (Figure 4B, left). ESA bands due to the −CN stretching modes are also visible but do not report on ES-SB along the D−A−D axis as the cyano groups are on an orthogonal axis.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Wang et al and other research groups successively reported the efficient near-infrared delayed fluorescence OLEDs using a DAD-type charge-transfer (CT) compound. Meanwhile, several corresponding donor–acceptor (DA)-type fluorescence chromophores have also been reported with comparable device performances. However, systematic studies are rarely reported on the differences of electronic and photophysical properties between DAD and DA-type fluorescence chromophores. In previous studies, symmetric quadrupolar DAD/ADA molecules that contain two or more electron donors or acceptor branches could undergo excited-state symmetry breaking (ESSB), that is, a transition from the symmetric multipolar to asymmetric dipolar states, and then exhibited the similar CT dynamics with single-branched DA analogue, such as solvatochromism. Herein we addressed this issue via a comparative study on the excited state dynamics of DA and DAD fluorescence systems (Figure ) in combination of theoretical calculations and transient absorption (TA) spectroscopy. Results show that DA and DAD molecular systems exhibit an almost identical excited state dynamics including similar fluorescence emission behaviors, which are attributed to the distinctive ESSB phenomenon observed in the DAD system.…”
mentioning
confidence: 99%